2013
DOI: 10.1177/1558689813479175
|View full text |Cite
|
Sign up to set email alerts
|

Using Concept Mapping in Community-Based Participatory Research

Abstract: Community-based participatory research (CBPR) has been identified as a useful approach to increasing community involvement in research. Developing rigorous methods in conducting CBPR is an important step in gaining more support for this approach. The current article argues that concept mapping, a structured mixed methods approach, is useful in the initial development of a rigorous CBPR program of research aiming to develop culturally tailored and community-based health interventions for vulnerable populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 36 publications
1
54
0
10
Order By: Relevance
“…The Board's focus on persons with a history of incarceration came from an organic process of meeting with NCCB members, conducting the needs assessment (see Windsor, 2013), and seeking funding. The PI found that NCCB members had intersecting needs (some working with drug abuse and HIV, others with previously incarcerated individuals, and others with HIV only).…”
Section: Resultsmentioning
confidence: 99%
“…The Board's focus on persons with a history of incarceration came from an organic process of meeting with NCCB members, conducting the needs assessment (see Windsor, 2013), and seeking funding. The PI found that NCCB members had intersecting needs (some working with drug abuse and HIV, others with previously incarcerated individuals, and others with HIV only).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, an action-oriented CBPR approach can create solutions that are then implemented by the communities and populations being studied (Olshansky, 2012). CBPR methods have been used to address a wide variety of social problems including HIV-related health disparities, food insecurity, substance use, recidivism, and sexual harassment (Berkley-Patton et al, 2010; Carney et al, 2012; Cheatham-Rojas & Shen, 2008; Windsor, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The NCCB was created in 2010 to promote research addressing health disparities and reentry issues in Newark, NJ. Over the past several years, the NCCB has developed and evaluated a manualized health intervention, called Community Wise , for people with a history of substance use returning to Newark from incarceration (Windsor, 2013; Windsor & Jemal, 2012; Windsor, Jemal, & Benoit, 2014; Windsor, Jessell, Lassiter, & Benoit, 2015; Windsor & Murugan, 2012; Windsor, Pinto, Benoit, Jessell, & Jemal, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…We also recommend the annotated bibliography of CBPR works by Julia Stevenson [89], and a review of three models of participatory research [88], and the journal publications offering rigorous methods, process, and outcomes in CBPR [71,91], and books on participatory research with practical applications [31], and health research [9].…”
Section: Introductionmentioning
confidence: 99%